SUCROSE AND SWADDLING EFFECTIVELY REDUCE PAIN RESPONSE ON NEONATAL BLOOD SPOT BY HEEL PRICK - Huda, Mega Hasanul; Yeni, Rustina; Nur, Agustini (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Pain stimulates distress emergence that potentially impairs the development and growth on neonates. Heel prick brings about pain. This research aimed at observing the effectiveness of sucrose and swaddling on pain response to neonates. Methods: A clinical trial was designed by random under control using cross-over design. This study involved 24 neonates (aged 28 days) which taken from population using a consecutive sampling technique. Each subject was given two treatments of sucrose (24%) and swaddling, but the pain responses were observed at different time during and after received the heel prick (1, 2, and 3 minutes). Response of neonatal pain focused on face observation, oxygen saturation, and heart rate, but scored by the experts using a set of observation sheets from Cries Neonatal Postoperative Pain Measurement Tool (CNPPMT). Results: During the heel prick, the average of pain response was found higher on sucrose group (2.67). After a minute elapsed, the average of pain response on both groups was similar (1.96). After two and three minutes elapsed, the average of pain response was found higher on swaddling group. Bivariate results showed that there was no different average of the pain response on both groups during the heel prick (p=0.925) and after the heel prick (one minute (p=0.915), two minutes (p= 0.942), and three minutes (p=0.132)). Conclusions: Research revealed that sucrose and swaddling equally effective in reducing pain response on neonatal blood spot by heel prick. Swaddling could be carried out to reduce pain response on infants when pricking applied.Â